Nutritional composition and antioxidant properties of three varieties of carrot (Daucus carota) - Nathaniel Owusu Boadi (Scientific African, 2021)
Carrots are a potentially rich source of antioxidants in addition to their nutritional properties. In this study, the nutritional composition and antioxidant properties of three varieties of carrots, namely Kuroda, Pamela and Amazonia cultivated in Ghana were determined. The peroxide scavenging method was used to determine the antioxidant properties of the ethanolic extracts of the carrot varieties at different concentrations. The protein, crude fibre, fat and carbohydrate contents of the carrot varieties ranged 6.46 – 10.73 %, 7.18 – 8.87 %, 1.97 – 4.31 % and 6.25 – 8.39 % respectively. The three varieties had high moisture contents ranging from 69.06 to 75.30 %. The antioxidant properties were high even at low concentrations of extract, and their activity increased with time in the order Amazonia > kuroda > pamela. Amazonia had the highest fibre, protein and carbohydrate contents and the lowest moisture content, making it the most preferred variety.